Implementasi Promosi Kesehatan dalam Program Penanggulangan Demam Berdarah Dengue (DBD) di Puskesmas Harapan Raya Pekanbaru - Nugraha, A. Fajri; Harahap, Heryudarini; Herniwanti (Badan Riset dan Inovasi Daerah (BRIDA) Provinsi Riau, 2018)
Dengue Hemorrhagic Fever (DHF) is one of the world's health problems and also becomes a public health problem in Indonesia which tends to be increasingly widespread.In Puskesmas Harapan Raya, DHF caseswere increase in three consecutive years. Various health promotion efforts have been carried out to reduce the number of DHF, but DHF cases remain high. The study aim was to assess the implementation of health promotion in the DBD prevention program in the Puskesmas Harapan Raya Pekanbaru. The study used a qualitative method.The main informants were health promotion program holders and P2P program holders in Pekanbaru City Health Services, the Head of the Puskesmas, health promotion program holders, and DHF program holder in Harapan Raya Health Center. Data was collected using interview and observation.The study showed human resources, facilities and infrastructure, funds were still a problem in the implementation of health promotion in the DHF prevention program at the health center.It was also found that health workers did not conduct counseling.Insufficient human resources, facilities and infrastructure as well as insufficient funds so that DBD promotion activities have not been optimal. It is suggested to the Puskesmas to maximize health workers by increasing the amount of human resources, facilities as well as funds in health promotion for DHF prevention.